Synthesis of ultrafine low loading Pd–Cu alloy catalysts supported on graphene with excellent electrocatalytic performance for formic acid oxidation. (1st April 2020) - Wang, Hou; Chen, Hui; Wang, Hui-Quan; Ou, Chang-Rui; Li, Run; Liu, Hong-Bo
Abstract: Here, surfactant free composite catalysts (Pd–Cu/rGO) with Pd–Cu alloy nanoparticles uniformly distributed on graphene sheets are successfully prepared via a facile hydrothermal approach. Compared with pure Pd/rGO catalyst, the introduction of copper could dramatically enhance the performance of the catalyst in the electrocatalytic formic acid oxidation (FAO) due to the strain effect and the ligand effect. With the optimized atomic ratio of 3:1 between palladium and copper, the alloy nanoparticle shows the smallest size of 2.12 nm, thus endowing the composite catalyst with highest catalytic efficiency. With Pd load as low as 14.5%, a maximum mass current density of 1580 mA mgPd −1, and residual current of 69.93 mA mgPd −1 at 3000 s was achieved with our Pd3 Cu1 /rGO catalyst in the electrocatalytic FAO process. Graphical abstract: Image 1 Highlights: A facile hydrothermal synthesis for surfactant-free PdCu/rGO composite catalysts was developed. The Pd3 Cu1 /rGO catalyst showed small particles size of 2.1 nm and narrow size distribution. The Pd3 Cu1 /rGO catalyst demonstrated the excellent electrocatalytic efficiency in the FAO process. The load amount of palladium in our Pd3 Cu1 /rGO was only 14.5%.